2022
DOI: 10.3390/nu14091779
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid 35 kDa Protects against a Hyperosmotic, Formula Feeding Model of Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC), an inflammatory disease of the intestine, is a common gastrointestinal emergency among preterm infants. Intestinal barrier dysfunction, hyperactivation of the premature immune system, and dysbiosis are thought to play major roles in the disease. Human milk (HM) is protective, but the mechanisms underpinning formula feeding as a risk factor in the development of NEC are incompletely understood. Hyaluronic acid 35 kDa (HA35), a bioactive glycosaminoglycan of HM, accelerates intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Consistent with our results, a previous study showed that hyaluronic acid could prevent dithizone-induced disruption of epithelial tight junctions. 44 Furthermore, in vitro experiments showed that both could restore the TEER value in the Caco-2 monolayer cell injury model, decrease the FD4 flux, and reduce intestinal epithelial permeability. Given that the expression of TJ proteins is dependent upon the MLCK/p-MLC pathway, myosin light chain kinase (MLCK) activation has been found to compromise the epithelial TJ barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, a previous study showed that hyaluronic acid could prevent dithizone-induced disruption of epithelial tight junctions. 44 Furthermore, in vitro experiments showed that both could restore the TEER value in the Caco-2 monolayer cell injury model, decrease the FD4 flux, and reduce intestinal epithelial permeability. Given that the expression of TJ proteins is dependent upon the MLCK/p-MLC pathway, myosin light chain kinase (MLCK) activation has been found to compromise the epithelial TJ barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ambitious preterm growth targets often necessitate the use of HM fortifiers, increasing the solute concentration of the infant diet. Fortification of HM, based largely on animal studies [ 84 , 85 ], is a suggested risk factor for classical NEC [ 86 ], but the risks associated with increased dietary osmolality may be further extended in the setting of CHD-associated intestinal ischemia [ 87 ]. Cognata et al demonstrated that an exclusively HM diet without fortification has been associated with a significant reduction in NEC risk preceding complex CHD repair [ 83 ].…”
Section: Practices For Initiation and Maintenance Of Enteral Feeds In...mentioning
confidence: 99%
“…Importantly, these three endpoints are all dysregulated in our lab’s NEC models. 57 , 58 , 60 , 61 , 64 , 70 Our data show that hBD2 is safe as an in vivo treatment in newborn mice with immature intestines. We also demonstrate that oral hBD2 given either before or after NEC induction as well as subcutaneous injection of hBD2 and oral LL-37 after NEC induction significantly decreased NEC injury scores.…”
Section: Discussionmentioning
confidence: 59%
“…To further determine the relevance of hBD2’s antimicrobial effects on prevention of experimental NEC, we used our recently described modification of the Paneth cell disruption NEC model with formula gavage replacing K. pneumoniae exposure as the second hit of the model. 57 , 58 , 64 Thus, this model does not use the addition of exogenous live bacteria to induce disease. In brief, P14-P16-day-old C57Bl/6J mice were fed a prepared rodent milk substitute formula (RMS) 57 , 58 , 65 1 h before receiving an intraperitoneal injection with dithizone as above, and then every 3 h for a total of four feeds.…”
Section: Resultsmentioning
confidence: 99%